The Design and Manufacture of DC-DC Full Bridge Converter with Mosfet-N Channel and Bipolar PWM Practical Module: Perancangan Dan Pembuatan Modul Praktikum Konverter DC-DC Full Bridge Dengan Mosfet-N Dan PWM Bipolar - Elia Yohan Yosefa (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2023)
By designation of the electrical engineering of engineering faculty at the Islamic University of Kadiri, the general directorate of the higher education ministry of national education should increase the facility as one of the supports to ensure the quality of the graduates in the field of their study. DC-DC converter applications have been selected as one of the lectures that must face by the college student. Therefore, it requires a module or device that has both practical and good reliability so that college students can understand DC-DC converter applications. The purpose of this research is design and manufacture an electronic laboratory that is a DC-DC Full Bridge Converter with Mosfet-N Channel and bipolar PWM also increases student’s competency through a practical class where they will use this module in an electronic laboratory. This research uses the flowchart method to during implementation can run systematically. The test divided into two-steps. First is PWM module and then the whole module where the output is DC motor controller. The results show that DC motor can be controlled very well. It was demonstrated when the duty cycle PWM control potentiometer lever was rotated in the far left, center, or even in the rightest position the direction and speed of the DC motor changed. Based on the result, it can be concluded that the DC-DC Full Bridge Converter with Mosfet-N Channel and Bipolar PWM bipolar designed using Mosfet IRF 540 and IC NE555 can control the direction and speed of the DC motor.